Research priorities for rehabilitation and aging with HIV: a framework from the Canada-International HIV and Rehabilitation Research Collaborative (CIHRRC) - O’Brien, Kelly K. (AIDS Res Ther, 2020)
BACKGROUND: People living with HIV are living longer, and can experience physical, mental and social health challenges associated with aging and multimorbidity. Rehabilitation is well positioned to address disability and maximize healthy aging. An international collaborative network, called the Canada-International HIV and Rehabilitation Research Collaborative (CIHRRC), works to guide this emerging field. In this article, we report findings from CIHRRC’s aim to identify emerging research priorities in HIV, aging and rehabilitation from the perspectives of people living with HIV, clinicians, researchers, representatives from community organizations and policy stakeholders. METHODS: We conducted a multi-stakeholder multi-method international consultation with people living with HIV, researchers, clinicians and representatives of community-based organizations to identify research priorities in HIV, aging and rehabilitation. Stakeholders identified research priorities during a one-day International Forum comprised of presentations and facilitated discussion. We collated and analyzed data using content analytical techniques, resulting in a framework of research priorities. RESULTS: Sixty-nine stakeholders from countries including Canada (n = 62; 90%), the United Kingdom (n = 5; 7%), United States (n = 1; 1%) and Australia (n = 1; 1%) attended the International Forum on HIV, Aging and Rehabilitation Research. Stakeholders represented community-based organizations (n = 20; 29%), academic institutions (n = 18; 26%), community or institutional healthcare organizations (n = 11; 16%), research or knowledge production organizations (n = 10; 14%), and organizations representing government or industry (n = 10; 14%). The Framework of Research Priorities in HIV, Aging and Rehabilitation includes seven research priorities: (1) nature, extent and impact of disability, concurrent health conditions and chronic inflammation with HIV; (2) prevalence, severity and impact of frailty; (3) community and social participation aging with HIV; (4) strategies for chronic disease management and healthy aging with HIV; (5) facilitators and barriers to access and engagement in, rehabilitation; (6) effectiveness of rehabilitation interventions for healthy aging with HIV; and (7) advancing development and use of patient reported outcome measures in HIV and aging. The Framework highlights methodological considerations to approach the priorities and the importance of knowledge translation and exchange to apply research knowledge into practice, programs and policy. CONCLUSIONS: These priorities offer a foundation for collaboration among international and multidisciplinary teams to advance the field of HIV, aging and rehabilitation in order to promote healthy aging with HIV.